2014
DOI: 10.1163/1568539x-00003122
|View full text |Cite
|
Sign up to set email alerts
|

Strategic and tactical fighting decisions in cichlid fishes with divergent social systems

Abstract: The costs and benefits of engaging in a contest will differ depending on the social situation of the individuals involved. Therefore, understanding contest behaviour can help to elucidate the trade-offs of living in differing social systems and shed light on the evolution of social behaviour. In the current study, we compared contest behaviour in two closely related species of Lamprologine cichlid fish. Neolamprologus pulcher and Telmatochromis temporalis are both pair-breeding cichlids, but N. pulcher are hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 72 publications
(96 reference statements)
1
39
0
Order By: Relevance
“…Between 0900 and 1700 hours, we observed each of these 40 focal subordinate fish for 10 min prior to capture and recorded all social behaviours produced and received. Following published ethograms for this species (Hick et al, 2014;Reddon et al, 2015;Sopinka et al, 2009), we categorized all social behaviours as overt physical attacks (ram, bite, mouth fight), restrained aggressive displays (operculum spreads, fin raises, head shakes), submissive displays (tail quivers, hook displays, submissive postures) or affiliative behaviours (parallel swims, follows, soft touches). We also recorded any aggression produced by the focal fish towards any heterospecific fish.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Between 0900 and 1700 hours, we observed each of these 40 focal subordinate fish for 10 min prior to capture and recorded all social behaviours produced and received. Following published ethograms for this species (Hick et al, 2014;Reddon et al, 2015;Sopinka et al, 2009), we categorized all social behaviours as overt physical attacks (ram, bite, mouth fight), restrained aggressive displays (operculum spreads, fin raises, head shakes), submissive displays (tail quivers, hook displays, submissive postures) or affiliative behaviours (parallel swims, follows, soft touches). We also recorded any aggression produced by the focal fish towards any heterospecific fish.…”
Section: Methodsmentioning
confidence: 99%
“…They also allow the signaller to remain in the same spatial location rather than fleeing from the dominant (Issa & Edwards, 2006;Ligon, 2014;Matsumura & Hayden, 2006). Consequently, the expression of submissive behaviour is essential for the formation and maintenance of stable groups (Hick, Reddon, O'Connor, & Balshine, 2014;Schenkel, 1967).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Conflict escalation within social groups can be avoided through the establishment of dominance hierarchies, the use of ritualized appeasement gestures or displays, or chemical signaling (Preuschoft and van Schaik 2000;van Wilgenburg et al 2005;Ratnieks et al 2006;Hick et al 2014). Encounters between social groups are more difficult to prevent from escalating, but if both sides benefit from it, mediating behavioral mechanisms can evolve (e.g., Neat et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…As physical contests require a significant investment in time and energy and have a potential cost of physical damage (Huntingford and Turner, 1987), animal social systems have evolved to avoid these, usually signaling with threats or postures that typically emphasize body size and often teeth. Comparing two closely related cichlid fish species from Lake Tanganyika, Hick et al (2014) found that highly social species were more likely to resolve disputes through submissive displays as compared with non-social species, suggesting that the dominance hierarchy formation is likely linked to the evolution of complex social systems.…”
Section: Dominance Hierarchies and Their Role In Social Evolutionmentioning
confidence: 99%